High-Throughput Chemical Screening Identifies Compounds that Inhibit Different Stages of the Phytophthora agathidicida and Phytophthora cinnamomi Life Cycles - Lawrence, Scott A.; Armstrong, Charlotte B.; Patrick, Wayne M.; Gerth, Monica L. (Frontiers in Microbiology, 2017)
Oomycetes in the genus Phytophthora are among the most damaging plant pathogens worldwide. Two important species are P. cinnamomi, which causes root rot in thousands of native and agricultural plants, and P. agathidicida, which causes kauri dieback disease in New Zealand. As is the case for other Phytophthora species, management options for these two pathogens are limited. Here, we have screened over 100 compounds for their anti-oomycete activity, as a potential first step towards identifying new control strategies. Our screening identified eight compounds that showed activity against both Phytophthora species. These included five antibiotics, two copper compounds and a quaternary ammonium cation. These compounds were tested for their inhibitory action against three stages of the Phytophthora life cycle: mycelial growth, zoospore germination and zoospore motility. The inhibitory effects of the compounds were broadly similar between the two Phytophthora species, but their effectiveness varied widely among life cycle stages. Mycelial growth was most successfully inhibited by the antibiotics chlortetracycline and paromomycin, and the quaternary ammonium salt benzethonium chloride. Copper chloride and copper sulfate were most effective at inhibiting zoospore germination and motility, whereas the five antibiotics showed relatively poor zoospore inhibition. Benzethonium chloride was identified as a promising anti-microbial, as it is effective across all three life cycle stages. While further testing is required to determine their efficacy and potential phytotoxicity in planta, we have provided new data on those agents that are, and those that are not, effective against P. agathidicida and P. cinnamomi. Additionally, we present here the first published protocol for producing zoospores from P. agathidicida, which will aid in the further study of this emerging pathogen.